logo

Ask Questions, Get Answers

X
 
Home  >>  EAMCET  >>  Mathematics

Observe the following statements:I. If $dy+2xy\;dx=2e^{-x^{2}} dx $ then $ye^{x^{2}}=2x+c$ II. If $ye^{-x^{2}}-2x=c$ then $dx=(2e^{-x^{2}}-2xy)dy$ Which of the following is a correct statement ?

(a) Both I and II are true. (b) Neither I nor II is true. (c)  I is true, II is false (d) I is false , II is true

1 Answer

(c) I is true, II is false
answered Feb 27, 2014 by meena.p
 

Related questions

Download clay6 mobile appDownload clay6 mobile app
...
X